PlantPure nation [videorecording (DVD)] : the truth is a stubborn thing. It doesn't go away - Forbes, Steve, 1947-; Campbell, T. Colin, 1934-; Campbell, Nelson (PlantPure Productions LCC, 2015)
The documentary film PlantPure Nation tells the story of three people on a quest to spread the message of one of the most important health breakthroughs of all time. After renowned nutritional scientist and bestselling author Dr. T. Colin Campbell gives a stirring speech on the floor of the Kentucky House of Representatives, his son Nelson, and Kentucky State Representative Tom Riner work together to propose a pilot program documenting the health benefits of a plant-based diet. Once the legislation goes into committee, agribusiness lobbyists kill the plan. Undeterred, Nelson decides to try his own pilot project in his hometown of Mebane, North Carolina.